PENERAPAN OUTDOOR LEARNING PROCESS (OLP) MENGGUNAKAN PAPAN KLASIFIKASI PADA MATERI KLASIFIKASI TUMBUHAN - Safitri, Okky Irmina; Retnoningsih, Amin; Irsadi, Andin (Journal of Biology Education, 2014)
Outdoor Learning Process (OLP) strategies which uses classification board to provide convenience and hands-on experience to the students so that learning more meaningful. This research aimed to know effective implementation of OLP on plant classification learning using classification boards in SMA N 1 Jekulo. Design research was a pre experimental study using One shot case study design. Sampling was determined by purposive sampling technique. Samples obtained by the class X1, X2 and X3 were numbered 114 students. Data obtained from student activity, student learning outcomes, the data the teacher and student responses. OLP value of learning activities was obtained from the observation the observer, while the value of mastery of the material derived from plant classification worksheet students and post-test scores. The results showed that the activity of 90% of students included in the category of active and very active. In the classical mastery learning has reached optimum set the standard â¥ 75%. Based on the results of this study concluded that OLP use media effectively learn the classification board applied to the material of plant classification. Â Strategi pembelajaran Outdoor Learning Process (OLP) menggunakan papan klasifikasi memberikan kemudahan dan pengalaman langsung pada siswa sehingga pembelajaran lebih bermakna. Penelitian ini bertujuan mengetahui efektivitas penerapan OLP pada pembelajaran klasifikasi tumbuhan menggunakan papan klasifikasi di SMA N 1 Jekulo. Desain penelitian adalah penelitian pre experimental menggunakan rancangan One shot case study. Pengambilan sampel ditentukan dengan teknik purposive sampling.Sampel yang diperoleh yaitu kelas X1, X2 dan X3 yang berjumlah 114 siswa. Data diperoleh dari aktivitas siswa, hasil belajar siswa, data tanggapan guru dan tanggapan siswa. Nilai aktivitas pembelajaran OLP diperoleh dari hasil pengamatan observer, sedangkan nilai penguasaan materi klasifikasi tumbuhan diperoleh dari lembar kerja siswa dan skor post-test. Hasil penelitian menunjukkan bahwa aktivitas siswa sebesar 90% termasuk dalam kategori aktif dan sangat aktif. Ketuntasan belajar secara klasikal telah mencapai standar optimal yang ditetapkan yaitu â¥ 75%. Berdasarkan hasil penelitian dapat disimpulkan bahwa OLP menggunakanÂ  media belajar papan klasifikasi efektif diterapkan pada materi klasifikasi tumbuhan. Â